(untitled) (Development Service Industry Management, 2023)
In this article a comprehensive systematization and further development of scientific research on the economic and intellectual potential at enterprises of network structures in the context of security conditions is carried out. To achieve this goal the dialectical method and the systematic approach to studying the features of economic and intellectual potential at enterprises of network structures were used. Monographic, abstract-logical, and abstraction methods were also used. As a result of the study, the main vectors of development the economic and intellectual potential at enterprises of network structures were determined, taking into account security aspects. Ways to increase the use of intellectual potential through cooperation with technology and innovation support centers were also identified. Research also points to the possibilities of developing branding as a way to increase the level of economic efficiency and increase the intellectual potential of enterprise. The results of the research can be applied for further scientific research and when making strategic decisions in the system of network structures. The conclusion of study is the need to implement new project solutions regarding the formation and realization of the economic and intellectual potential at enterprises of network structures, as they are characterized by a high level of dynamism and novelty.